ANALYZING THE SPELLING MISTAKES IN STUDENTS’ ESSAY IN INDONESIANSUBJECT AT GRADE IV OF ELEMENTARY SCHOOL - Dwi Yanti; Hetilaniar; Susanti Faipri Selegi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
Writing essays is one of the writing skills taught to grade IV students at SD Negeri 26 Talang Kelapa. However, many spelling mistakes were still found in students' writings. For this reason, the problem in this study was the spelling mistakes found in students' essays in the Indonesian subject at grade IV of elementary schools. The purpose of this study was to describe the spelling mistakes found in students' essays in the Indonesian subject at grade IV of elementary school. The object of this study was the spelling mistakes found in the students' essays. The informants in this study were students and teachers of class IV SD Negeri 26 Talang Kelapa Kabupaten Banyuasin. This research utilized a qualitative descriptive method. Data were collected through documentation and interviews. The data were analyzed through data reduction, data presentation, and conclusion drawing. The results of this study indicated that the mistakes were in using capital letters, full stops, commas, and pronouns. This occurred because students did not understand the correct spelling in writing. The students had difficulties in writing essays since they paid less attention to the teacher's explanations in Indonesian subjects. Thus, teachers needed to improve students' understanding of the use of spelling.